Macroscopic excitation energy transport in a structured Co nanolayer - Khmelinskii, Igor (2019)
We report absorption spectra of the 7.3-and 11.3-nm Co nanolayers and emission of a structured Co nanolayer. The structure contains a 7.3-nm Co nanolayer covering a 25 x 25 mm(2) fused silica substrate, with a thicker 11.3-nm Co track in the middle of the substrate. We report that the radiation energy absorbed by the entire Co nanolayer is transferred to the thicker nanotrack. The transferred energy is reemitted by the track, with the emission spectra containing well-defined emission bands, strongly dependent on the excitation wavelength. We report that the bands appearing in the emission spectra of the nanotrack correspond to the transitions from the higher electronic excited states of the nanotrack to its first excited state. We therefore identify the observed emission as the superemission of the Co nanotrack. The superemission quantum yield is dependent on the excitation wavelength, decreasing at higher excitation energies. We propose a theoretical model that explains the results obtained. The model analysis produced estimates of several model parameters.